2006
DOI: 10.1063/1.2177627
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility bottom-contact n-channel organic transistors and their use in complementary ring oscillators

Abstract: The electrical characteristics of bottom-contact organic field-effect transistors fabricated with the air-stable n-type semiconductor N,N′-bis(n-octyl)-dicyanoperylene-3,4:9,10-bis(dicarboximide) (PDI-8CN2) are described. The mobility, threshold voltage, subthreshold swing, and Ion∕Ioff ratio(VDS=40V, VG=0∼40V) are 0.14cm2∕Vs, 1.6V, 2.0V/decade, and 1.2×103, respectively. The effect of electrode/dielectric surface treatment on these devices is also examined, with a combination of 1-octadecanethiol and hexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 21 publications
5
94
0
Order By: Relevance
“…For example, the crystal structure of an edible ingredient can influence its taste and texture; in the pharmaceutical industry, different crystal polymorphs of the same drug can have drastically different dissolution rates, bioavailability and chemical stability 2,6 . In the field of organic electronics, small aromatic molecules are widely used as the organic semiconductors (OSCs) for thin-film transistors (TFTs) to fabricate a variety of flexible, transparent and bendable electronics [7][8][9][10][11][12] . The OSC chemical structure, together with p-p stacking and van der Waals intermolecular interactions, collectively determine the molecular packing structure.…”
mentioning
confidence: 99%
“…For example, the crystal structure of an edible ingredient can influence its taste and texture; in the pharmaceutical industry, different crystal polymorphs of the same drug can have drastically different dissolution rates, bioavailability and chemical stability 2,6 . In the field of organic electronics, small aromatic molecules are widely used as the organic semiconductors (OSCs) for thin-film transistors (TFTs) to fabricate a variety of flexible, transparent and bendable electronics [7][8][9][10][11][12] . The OSC chemical structure, together with p-p stacking and van der Waals intermolecular interactions, collectively determine the molecular packing structure.…”
mentioning
confidence: 99%
“…While operating under vacuum, a saturation regime mobility of 2. [12] because of morphological/microstructural irregularities; however, it is the highest organic n-channel solution-processed OFET mobility obtained to date for channel lengths smaller than 10 lm.…”
Section: Nn′-bis(n-octyl)-(17and16)-dicyanoperylene-34:910-bis(dicar-mentioning
confidence: 94%
“…The enabling advance reported here is the successful development of an air-stable n-type organic semiconductor, PDI-8CN 2 , along with compatible solution-deposition processing techniques. Experimental PDI-8CN 2 was synthesized and purified as reported previously [11,12]. The compound was pure, as confirmed by 1 H NMR and elemental analysis.…”
Section: Nn′-bis(n-octyl)-(17and16)-dicyanoperylene-34:910-bis(dicar-mentioning
confidence: 99%
See 1 more Smart Citation
“…N , NЈ-dialkyl-3,4,9,10-perylene tetracarboxylic diimide ͑PTCDI-Cn͒, especially, is very promising n-type materials with a high electron mobility, and studied intensively from the first stage of researches on OTFTs. [14][15][16][17][26][27][28][29][30][31][32][33][34][35][36][37][38][39] For example, Horowitz et al have reported the first n-type organic TFT made of N , NЈ-diphenyl PTCDI 14 yr ago. 26 After 6 yr, Malenfant et al have reported a N,NЈ-dioctyl PTCDI TFT with fairly high electron mobility as high as 0.6 cm 2 / V s. 27 Jones et al have synthesized corecyanated PTCDI with fluorinated alkyl chains, and reported an air-stable TFT with electron mobility of 0.64 cm 2 / V s. 28 Chesterfield et al have reported strikingly high electron mobility in N , NЈ-dioctyl PTCDI TFT of up to 1.7 cm 2 / V s through exquisite control of deposition condition, 29 and after that many research groups have poured their efforts to develop high-mobility n-type PTCDI OTFTs by modifying the molecular structure with core-substitution or with changing the substituent on the imide N atoms, by controlling deposition condition, by optimizing device structure such as the surface state of dielectrics and electrode contact, and so on.…”
Section: Introductionmentioning
confidence: 99%